MANAJEMEN PEMERINTAHAN DINAS PARIWISATA DALAM PEMBANGUNAN WISATA SEJARAH DI KABUPATEN SIAK 2016-2017 - Putra, Nugraha Dhanasyah; Febrina, Rury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The research entitled "Government Management of the Tourism Office in the Development of Historical Tourism in Siak Regency 2016-2017" This research is based on the Siak Regency Regional Regulation Number 13 of 2012 concerning the Regional Tourism Development Master Plan (RIPPDA) of Siak Regency Article 13 activities that "Tourism Strategic Areas I for the development of tourism products based on historical and cultural heritage tourism supported by culinary tourism in one unit, the development of â€œHistory and Cultureâ€ tourism in the coverage of Siak District â€. Siak District is the focus of tourism in the historical and cultural tourism sector, therefore every historical tourism object in Siak District is the main focus of management by the Siak Regency Tourism Office. as for the formulation of the problem in this study is "How the Governance of the Siak Regency Tourism Office in Historical Tourism Development"The method used in this research is a qualitative method which describes the data descriptively. The data techniques used were interviews and documentation. While the data source used is primary data obtained from the research location in the form of research information and then support secondary data in the form of document data.The results showed that the management of historical tourism objects in the Siak Regency Tourism Office was good in historical tourism objects. Three indicators that go well are planning, monitoring, organization, while what is not good is the implementation, therefore it is necessary to improve in order to increase tourists and services to historical tourism in Siak district. It is undeniable that other indicators have also increased.Â Â Keywords: Tourism, Government Management, Historical Tourism